2021
DOI: 10.1016/j.apsb.2021.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the biological functions and medical applications of extracellular vesicles and analogues

Abstract: Natural extracellular vesicles (EVs) play important roles in many life processes such as in the intermolecular transfer of substances and genetic information exchanges. Investigating the origins and working mechanisms of natural EVs may provide an understanding of life activities, especially regarding the occurrence and development of diseases. Additionally, due to their vesicular structure, EVs (in small molecules, nucleic acids, proteins, etc.) could act as efficient drug-delivery carriers. Herein, we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 249 publications
0
34
0
Order By: Relevance
“…However, viral vectors have disadvantages as well, e.g., the phage vector has a low loading capacity and needs sufficient studies, while in the case of lentiviral vectors, random genomic integration might result in the insertional mutation [ 231 ]. In terms of non-viral delivery systems, the exosome-based method is one of the most promising [ 231 ], although the difficulty of preparation hinders its development [ 232 ]. In hair growth studies, mostly lipofectamine (in vitro) [ 7 , 76 , 177 , 189 , 190 ] and in vivo jetPEI [ 77 ] are used as delivery systems.…”
Section: Main Challenge: Delivery Systemsmentioning
confidence: 99%
“…However, viral vectors have disadvantages as well, e.g., the phage vector has a low loading capacity and needs sufficient studies, while in the case of lentiviral vectors, random genomic integration might result in the insertional mutation [ 231 ]. In terms of non-viral delivery systems, the exosome-based method is one of the most promising [ 231 ], although the difficulty of preparation hinders its development [ 232 ]. In hair growth studies, mostly lipofectamine (in vitro) [ 7 , 76 , 177 , 189 , 190 ] and in vivo jetPEI [ 77 ] are used as delivery systems.…”
Section: Main Challenge: Delivery Systemsmentioning
confidence: 99%
“…Starting from 2006, several groups reported that EVs could contain and transfer biomolecules present in the cytosol of originating cells [ 1 ], including mRNA and miRNA [ 2 ], proteins, lipids and metabolites [ 3 ]. The bioactive materials are protected by the vesicles from the extracellular environment and shuttled to neighboring or considerably distant cells, triggering functional changes in the recipient cells and regulating many physiological and pathological processes [ 4 ]. The discovery of their role of intercellular messengers, made EVs compelling candidates for the development of innovative therapeutic tools.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to these promising features, EVs have been recently evaluated as efficient carriers for the delivery of therapeutic cargos like small molecule drugs, nucleic acids, genes and even NPs for the treatment of various pathologies, including neurodegenerative and cardiovascular diseases, inflammation, diabetes [ 4 ] and especially cancer. According to a query done on July 2021 on the US-NIH clinical trials database, 324 clinical trials on EVs or exosomes are currently registered, 121 of which refer to their use for both diagnostic and therapeutic oncological purposes.…”
Section: Introductionmentioning
confidence: 99%
“…EXOs are endogenous extracellular nanovesicles deriving from the endosomal system with a particle size ranging from 30 to 150 nm. EXOs are released by various types of cells into the extracellular environment as nature’s nano delivery system of lipids, proteins, and nucleic acids, playing an important role in intercellular communication 134 , 135 , 136 , 144 .…”
Section: Sirna Delivery Systems For Treatment Of Ali/ardsmentioning
confidence: 99%